Can cone-beam computed tomography superimposition help orthodontists better understand relapse in surgical patients? - Porciuncula, Guilherme Machado [UNESP]; Koerich, Leonardo; Eidson, Lindsey; Gandini Júnior, Luiz Gonzaga [UNESP]; Gonçalves, João Roberto [UNESP] (Elsevier B.V., 2014)
This case report describes the interdisciplinary treatment of a 19-year-old Brazilian man with a Class I malocclusion, a hyperdivergent profile, an anterior open bite, and signs of temporomandibular joint internal derangement. The treatment plan included evaluation with a temporomandibular joint specialist and a rheumatologist, orthodontic appliances, and maxillomandibular surgical advancement with counterclockwise rotation. Cone-beam computed tomography images were taken before and after surgery at different times and superimposed at the cranial base to assess the changes after orthognathic surgery and to monitor quantitatively the internal derangement of the temporomandibular joints and surgical relapse. Our protocol can improve the orthodontist's understanding of surgical instability, demonstrate the clinical value of cone-beam computed tomography analysis beyond the multiplanar reconstruction, and guide patient management for the best outcome possible.